Decision Support System for Direct Target Cash Recipients Using the AHP and K-Means Method - Teguh Sri Pamungkas; Agus Susilo Nugroho; Ichsan Wasiso; Tri Anggoro; Kusrini Kusrini (RESEARCH : Journal of Computer, Information System & Technology Management, 2020)
In the Covid-19 pandemic situation, the government organized a Direct Cash Assistance as known as BLT for the people who were affected by Covid-19. The nominal amount of BLT received by the public is Rp. 600,000 per month. But in fact, the amount of BLT quota is not proportional to the list of BLT recipients submitted by regional officials, in this case, RT (Rukun Tetangga). So, to find out who is really suitable or appropriate, a decision-making system is needed so that the deposit of the BLT from the government can be right on target in accordance with the criteria set by the government. Stages of the study began with clustering of weights. After that, it is entered into the system to do a decision support process with AHP (Analytical Hierarchy Process). The target of this research is the application that can be used to assist the government in distributing BLT to be right on target. Based on the functional testing of the system, the functions in the system have been succeeded according to plan. This system has successfully applied the K-Means and AHP methods for decision making, to receive direct cash assistance from the government. This system has a 100% accuracy rate. Where the most important criteria in this system are income with a weight of 0.394142515, ownership of a house with a weight of 0.231035138, number of dependents with a weight of 0.190359096, age with a weight of 0.081077616, employment with a weight of 0.058111736, and weight with a weight of 0, 045273898